Bioenergetic responses mediate interactive effects of pharmaceuticals and warming on freshwater arthropod populations and ecosystem functioning - Duchet, Claire; Verheyen, Julie; Van Houdt, Ria; Grabicová, Kateřina; Dekan Carreira, Vladimíra; Stoks, Robby; Boukal, David S (Journal of hazardous materials, 2025)
Freshwater ecosystems are increasingly impacted by pharmaceutical contaminants (PhACs) and climate change-induced warming. Yet, their joint effects on freshwater taxa remain unclear. This is partly due to poorly understood mechanisms linking the effects on (sub)individual scales to higher levels of ecological organisation. We investigated the responses of two aquatic arthropods, Asellus aquaticus and Cloeon dipterum, to environmentally realistic levels of a 15-PhAC mixture (total concentration: 2.9 µg/L) and warming (+4 °C above ambient) in outdoor pond mesocosms (1000 L) across winter and summer. We measured physiological traits (bioenergetic responses based on quantification of energy consumption and energy stored in proteins, sugars and lipids, and oxidative damage based on malondialdehyde [MDA] levels), population density and ecosystem functions (leaf litter decomposition and insect emergence). In winter, PhACs reduced energy availability and increased MDA levels. In contrast, PhACs increased energy availability and decreased MDA levels in summer. The stressors reduced Asellus abundance, leading to reduced leaf litter decomposition, while Cloeon emergence in summer declined due to a PhAC-induced decline in larval abundance. Warming alone consistently decreased arthropod abundances and emergence, except for Asellus abundance in winter. The stressor effects through changes in bioenergetics were stronger than their direct effects on population abundances and ecosystem functions. Our findings highlight the vulnerability of aquatic arthropods to PhAC pollution and warming, emphasising the need for effective management strategies to mitigate the effects of emerging contaminants and climate change on freshwater biota.
Keywords: Climate change; Ecological impacts; Animals; Energy budget; Climate Change; Seasons; chemické látky znečišťující vodu; klimatické změny; Water Pollutants, Chemical; energetický metabolismus; Cloeon; členovci; Freshwater invertebrates; Energy Metabolism; roční období; Fresh Water; Arthropods; Oxidative stress; Asellus; Xenobiotics; sladká voda; ekosystém; Ecosystem; zvířata